Needs and Challenges for Online Language Teachers – The ECML Project DOTS - Beaven, Tita (Array, 2010)
The growing use of digital technologies in educational settings, paralleled by a paradigm change in educational theory from an instructivist transmission approach to constructivist and sociocultural theories of learning, demands more adapted teacher training programs, both technical and pedagogical. Looking at factors influencing teachers’ implementation of ICT in the foreign language classroom and guided by the results of a needs analysis survey conducted among twenty six language teachers from twenty five different European countries, the DOTS project aims to develop an online workspace with bite-sized learning objects for autonomous use by language professionals, particularly freelance teachers who frequently miss out on the training opportunities provided for their full-time colleagues.